INCIDENCE OF CONTRAST-INDUCED ACUTE KIDNEY INJURY AND ASSOCIATED FACTORS IN PATIENTS AGED≥65 WITH CHRONIC KIDNEY DISEASE AND ACUTE CORONARY SYNDROME UNDERGOING PERCUTANEOUS CORONARY INTERVENTION - Văn Vinh, Châu; Đình Giảng, Phạm; Văn Tín, Đinh; Văn Tân, Nguyễn (Journal of Health and Aging, 2025)
Contrast-induced nephropathy (CIN) is a common complication following percutaneous coronary intervention (PCI), particularly in older patients with chronic kidney disease (CKD) and acute coronary syndrome (ACS). CIN can lead to worsening renal function, increased mortality, and prolonged hospitalization. However, data on the incidence and associated factors of CIN in this high-risk population remain limited. To determine the incidence and associated factors of CIN in patients aged ≥65 years with CKD and ACS undergoing percutaneous coronary intervention (PCI). A prospective descriptive study enrolled 225 patients aged ≥65 years with CKD and ACS admitted to Thong Nhat Hospital from May 2024 to May 2025. Serum creatinine and estimated glomerular filtration rate (eGFR) were monitored before and up to five days post-PCI. CIN is defined as an increase in creatinine ≥25% or ≥0.5 mg/dL from baseline. Risk factors analyzed include the Mehran risk score, cardiovascular history, hemodynamic status, anemia, and contrast volume. CIN occurs in 13.8% of patients, with significantly higher incidence in CKD stage 4–5 compared to stage 3 (23.3% vs. 9.2%; p = 0.004). The CKD 4–5 group has a higher mean Mehran score (15.4 vs. 7.31; p = 0.001) and lower post-PCI eGFR (16.8 vs. 46.6 mL/min/1.73 m²; p < 0.001). Two patients (0.9%) require emergency dialysis, and in-hospital mortality is 1.8%, mostly among those with advanced CKD. Significant predictors of CIN include Mehran score ≥10, heart failure, anemia, hypotension, and higher contrast volume. CIN remains a relevant complication in elderly patients with CKD and ACS undergoing PCI, especially in those with advanced CKD. Early risk stratification, hemodynamic optimization, and careful management of contrast use are essential to reducing CIN in this high-risk group.